Brill's Companion to the Reception of Plutarch - Sophia Xenophontos; Katerina Oikonomopoulou (Brill's Companions to Classical Reception, 2019)
The Greek biographer and philosopher Plutarch of Chaeronea (c. 45-125 AD) makes a fascinating case-study for reception studies not least because of his uniquely extensive and diverse afterlife. Brill's Companion to the Reception of Plutarch offers the first comprehensive analysis of Plutarch's rich reception history from the Roman Imperial period through Late Antiquity and Byzantium to the Renaissance, Enlightenment and the modern era. The thirty-seven chapters that make up this volume, written by a remarkable line-up of experts, explore the appreciation, contestation and creative appropriation of Plutarch himself, his thought and work in the history of literature across various cultures and intellectual traditions in Europe, America, North Africa, and the Middle East.